Enter the worship circle - Pasley, Ben. (Lake Mary, Fla. : Relevant Books, 2001)
This spiritual journey is written in the language of a generation that, having divorced religion, is still desperate to build a relationship with God.
Keywords: Spirituality; Spiritual life; Christian life